INOVASI LAYANAN PERBANKAN PADA ERA DISRUPTION DI KOTA DAN KABUPATEN SUKABUMI - Anugrah, Ce Mulya Rizki; Royani, Ida (2021)
Changes in consumer preferences from conventional to internet users, changes in regulations on increasingly challenging macroeconomic conditions and the number of fintech companies are very hard homework for the banking world, especially to serve its customers, apart from demanding that banks transform into digital banking. Innovation and services hold the key to customer satisfaction in conducting transactions at the Bank.The absence of new innovations will make customers saturated with existing products and when the Bank's services are not satisfactory, customers will tend to move to other banks. Moreover, the presence of fintech companies is a challenge for the banking world in maintaining its existence. That is the important role of service and innovation in creating a good image for the company with the aim of fostering customer loyalty which will have an impact on company profits.To answer the research objectives, this study uses quantitative research methods and to obtain data using online questionnaires to respondents. The research sample taken is 400 samples, namely customers who save at Bank BCA, Bank Mandiri, Bank BNI and Bank BRI in the City and District of Sukabumi where the primary data is processed using Structural Equation Modeling or SEM.The conclusion of the overall measurement of the results of the goodness of fit index model presented above indicates that the model is well accepted even though the Chi Square, Probability and DF values ​​are not fit but can be compensated for by other models such as GFI, AGFI, CLI, TLI and RMSEA.